2017
DOI: 10.1149/2.1221709jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Filiform Corrosion of Mg–3Zn Mg Alloy

Abstract: The filiform corrosion of Mg-3Zn Mg alloy in various corrosion environments was investigated by scanning electron microscopy (SEM) observations, scanning vibrating electrode technique (SVET) and electrochemical measurements. The results indicate that corrosion filaments can cross grain boundaries and fine precipitation phases to develop continually. The propagation of filiform corrosion is greatly associated with the existence of Cl − in the solutions. A small amount addition of F − or SO 4 2− to the NaCl solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…The second phase in the grain boundaries and the Zr-rich region within the grains have an essential influence on the origination and propagation of the corrosion filaments on the cast ZK60. These filiform-like corrosion characteristics of the cast ZK60 were quite different from those of Mg-3Zn and Mg-8Li alloys reported previously [ 65 , 71 ], in which the corrosion filaments seem not to be affected by the second phases and can originate from the center of the grains and spread to various directions. These differences should be ascribed to their different microstructures, especially the quantity and size of the second phase and the distribution of alloying elements in these alloys.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The second phase in the grain boundaries and the Zr-rich region within the grains have an essential influence on the origination and propagation of the corrosion filaments on the cast ZK60. These filiform-like corrosion characteristics of the cast ZK60 were quite different from those of Mg-3Zn and Mg-8Li alloys reported previously [ 65 , 71 ], in which the corrosion filaments seem not to be affected by the second phases and can originate from the center of the grains and spread to various directions. These differences should be ascribed to their different microstructures, especially the quantity and size of the second phase and the distribution of alloying elements in these alloys.…”
Section: Discussioncontrasting
confidence: 89%
“…Only Mg, O, and Cl elements were found in the corrosion product layer, which should result from Mg(OH) 2 and Cl − in the test solution. Moreover, a large number of Cl − through the whole corrosion product layer suggests that Cl − could penetrate the product layer easily and may become enriched in the bottom of the corrosion pit to propagate the pit corrosion [ 71 ]. The second-phase particles in the corrosion pit imply that they may be related to the formation of corrosion pits, which is discussed later.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the corroded area took the form of filiform-like corrosion. This type of corrosion attack is characteristic of the proliferation of the corrosion under the coating or under the created layer of corrosion products in the case of untreated AZ31 magnesium alloy [47]. The corrosion products covered the whole surface after 168 h of sample immersion in SBF solution, Figure 9.…”
Section: Immersion Testsmentioning
confidence: 98%
“…During the test, the sample surface was observed to determine the hydrogen gas generated on the entire surface of the cathode, whereas filiform-type corrosion was observed at the anode with hydrogen gas generated at the tip of the filament. Wang et al 15) evaluated the filiform corrosion of a MgZn alloy in a 2.5-mM NaCl solution by SVET and reported that the tip of the filament is the anode. After 24 h, a region exhibiting white or its opposite color was generated on both anode and cathode, suggesting that the polarity involved in galvanic corrosion has changed in this section.…”
Section: Svetmentioning
confidence: 99%